Diacylglycerol kinase κ (DGKK) variants and hypospadias in Han Chinese: association and meta‐analysis. (24th May 2015) - Ma, Qichao; Tang, Yunman; Lin, Houwei; Xu, Maosheng; Xu, Guofeng; Fang, Xiaoliang; Chen, Jianhua; Song, Zhijian; Li, Zhiqiang; Shi, Yongyong; Geng, Hongquan
<x xml:space="preserve">Abstract</x> Objective To investigate whether diacylglycerol kinase κ (DGKK) is a susceptibility gene for hypospadias in the Han Chinese population as has been suggested by previous publications. Patients Subjects and Methods A case‐control study involving 466 patients with hypospadias and 402 healthy subjects was conducted to assess the relationship between DGKK single nucleotide polymorphisms (SNPs) and hypospadias risk in the Han Chinese population. The 466 hypospadias patients were further divided into mild, moderate and severe subgroups for analysis. Results Six SNPs (rs1934179, rs4143304, rs9969978, rs1934188, rs4826632 and rs4599945) were marginally associated with mild and moderate hypospadias [odds ratios (ORs) > 1, P = 0.05 to P < 0.1), whereas no significant relationship was seen with the severe cases (ORs >1, P > 0.1). After correcting for multiple testing, it was determined that neither individual SNPs nor individual haplotypes were associated with hypospadias. To evaluate this relationship in multiple populations, we performed a meta‐analysis on six SNPs, using combined data from our present results and those of previous studies of different races (including 1966 patients and 2492 controls). Six SNPs (rs1934179, rs4143304, rs9969978, rs1934188, rs7063116 and rs1934190) were significantly associated with mild/moderate hypospadias (ORs >1, P < 0.05), and rs1934179 was significantly associated with severe hypospadias (OR > 1, P < 0.05). Conclusions DGKK gene variants do not appear to play a major role in hypospadias susceptibility in the Chinese Han population. Our meta‐analysis supports the hypothesis that DGKK is a common risk gene for hypospadias, particularly in cases of mild or moderate hypospadias in Caucasian populations.